Development and Pilot Testing of a Childbirth Readiness Questionnaire (CRQ) for Third-Trimester Pregnant Women In Indonesia - Nurul Jannah; Gunavathy Selvarajh (PT Inovasi Pratama Internasional, 2026)
Childbirth readiness is a multidimensional construct encompassing physical, psychological, social, and spiritual preparedness, yet contextually appropriate instruments for Indonesian pregnant women remain limited. This study aimed to develop and pilot test the Childbirth Readiness Questionnaire (CRQ) for third-trimester pregnant women in Indonesia. A methodological pilot design was employed, including expert review (n = 5) and field testing with 110 pregnant women. Content validity was evaluated using the Item Content Validity Index (I-CVI), while preliminary construct performance was examined through descriptive statistics and corrected item–total correlations. Internal consistency reliability was assessed using Cronbach’s alpha. All nine items demonstrated acceptable content validity (I-CVI ≥ 0.80) and adequate item–total correlations (r = 0.34–0.61). The overall scale showed satisfactory internal consistency (α = 0.82). Dimension-level descriptive scores supported the conceptual structure of physical–cognitive, psychological–spiritual, and social support readiness. These findings indicate that the CRQ has promising preliminary psychometric properties and is feasible for assessing childbirth readiness among Indonesian third-trimester pregnant women. Further validation with larger and more diverse samples is required to confirm its factorial structure and generalizability